THE IMPLEMENTATION OF PEER-REVIEW TECHNIQUE IN AN EFL WRITING CLASS - Wiwit Rianti (Journal of English Education Program (JEEP), 2017)
This study gave a report on the implementation of peer-review technique in teaching EFL writing conducted in the second level of English Program of a Private University. This study aimed at finding out the implementation of peer-review technique in an EFL writing class, finding out the reasons of the lecturer for using peer-review technique in teaching creative writing, and finding out the students’ perceptions on the implementation of peer-review technique in writing class. To investigate the students’ problems, the writer proposed three research questions: (1) how does the lecturer implement peer-review technique in an EFL writing class?  (2) why does the lecturer use peer-review technique in teaching writing? (3) what are the students’ perceptions on the implementation of peer-review technique in writing class? To get the data, the writer employed case study design. Based on the result of the study, it showed that peer-review technique can help the students to improve their EFL writing class. Besides that, the students can increase their critical thinking through peer-review technique. Finally, based on the results above, the writer suggested that English lecturer had to implement peer-review technique to improve students’ critical thinking in writing.